Geographic decomposition of inequality in health and wealth: Evidence from Cambodia - FUJII, Tomoki (Institutional Knowledge at Singapore Management University, 2013)
Applying the small-area estimation methods to Cambodia data, we decompose the total inequality in wealth (consumption) and health (child undernutrition) indicators into within-location and between-location components. Because the knowledge of the pattern of spatial disparity in poverty and undernutrition is important for the geographic targeting of resources, we conduct a geographic decomposition of the variance of the Foster-Greere-Thorbecke index in addition to the standard decomposition exercise based on the generalized entropy measures. We find that a sizable proportion of wealth inequality is due to between-location inequality, whereas health inequality is mainly due to within-location inequality.